Female Circumcision: Mopolihu Lo Limu and Mongubingo Customs in Building Leadership Behavior - Lisdawati Muda (UIN Maulana Malik Ibrahim Malang, 2020)
This article discusses the custom of female circumcision for the people of Gorontalo, carried out for generations. The procession of female circumcision custom process has its symbol, meaning, and purpose, that expects every circumcised girl to be a religious woman, useful for family, community, nation-state life. Besides, she is expected to have a responsible and trustworthy leader spirit. The role of women as leaders and how to behave in leadership is reflected in the custom practices of female circumcision. The results showed that in the perspective of the Gorontalo community, the female circumcision tradition is an obligation because of its values as a translation of religious importance. The persistence of Gorontalo people to always preserve this tradition is maintained, even though some scholars and communities view that female circumsicion is not a compulsory matter. Artikel ini membahas mengenai adat khitan perempuan bagi masyarakat Gorontalo yang dilakukan secara turun temurun. Urutan prosesi adat khitan perempuan memiliki lambang, arti dan maksud tersendiri, yakni mengharapkan setiap anak perempuan yang dikhitan menjadi perempuan yang taat beragama, bermanfaat bagi kehidupan keluarga, masyarakat, bangsa dan negara. Selain itu, mereka diharapkan berjiwa pemimpin yang bertanggung jawab dan dapat dipercaya. Peran perempuan sebagai seorang pemimpin dan bagaimana berperilaku dalam memimpin tercermin dalam tata cara adat khitan perempuan. Hasil penelitian menunjukkan bahwa dalam pandangan hidup masyarakat Gorontalo, adat khitan perempuan adalah suatu kewajiban karena nilai-nilai yang terkandung di dalamnya merupakan penjabaran nilai-nilai agama. Keteguhan masyarakat Gorontalo untuk selalu melestarikan adat khitan perempuan tetap terjaga, meskipun dalam pandangan sebagian ulama dan sebagian masyarakat khitan perempuan bukan merupakan perkara wajib yang harus dilakukan